Scientific evidence is just the starting point: A generalizable process for developing sports injury prevention interventions - Alex Donaldson; David G. Lloyd; Belinda J. Gabbe; Jill Cook; Warren Young; Peta White; Caroline F. Finch (Elsevier, 2016)
Background: The 2 most cited sports injury prevention research frameworks incorporate intervention development, yet little guidance is available in the sports science literature on how to undertake this complex process. This paper presents a generalizable process for developing implementable sports injury prevention interventions, including a case study applying the process to develop a lower limb injury prevention exercise training program (FootyFirst) for community Australian football. Methods: The intervention development process is underpinned by 2 complementary premises: (1) that evidence-based practice integrates the best available scientific evidence with practitioner expertise and end user values and (2) that research evidence alone is insufficient to develop implementable interventions. Results: The generalizable 6-step intervention development process involves (1) compiling research evidence, clinical experience, and knowledge of the implementation context; (2) consulting with experts; (3) engaging with end users; (4) testing the intervention; (5) using theory; and (6) obtaining feedback from early implementers. Following each step, intervention content and presentation should be revised to ensure that the final intervention includes evidence-informed content that is likely to be adopted, properly implemented, and sustained over time by the targeted intervention deliverers. For FootyFirst, this process involved establishing a multidisciplinary intervention development group, conducting 2 targeted literature reviews, undertaking an online expert consensus process, conducting focus groups with program end users, testing the program multiple times in different contexts, and obtaining feedback from early implementers of the program. Conclusion: This systematic yet pragmatic and iterative intervention development process is potentially applicable to any injury prevention topic across all sports settings and levels. It will guide researchers wishing to undertake intervention development.